Welfare regime and social class variation in poverty and economic vulnerability in Europe: An analysis of EU-SILC - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2009)
In this paper we address a set of interrelated issues. These comprise the relative merits of unidimensional versus multidimensional approaches to poverty and social exclusion, increasing concerns about reliance on nationally based income poverty measures in the context of EU-enlargement and the continuing relevance of class based explanations of variation in life chances. Employing the EU-SILC data set, we identify for each of a set of welfare regimes a group of economically vulnerable individuals. Contrary to the situation with national income poverty measures, levels of economic vulnerability vary systematically across welfare regimes. The multidimensional profile of the economically vulnerable sharply differentiates them from the remainder of the population. Unlike the national relative income approach, the focus on economic vulnerability produces a pattern of class differentiation that is not dominated by the contrast between the property owning classes and all others. In contrast to a European-wide relative income approach, it also simultaneously captures the fact that absolute levels of vulnerability are distinctively high among the lower social classes in the less affluent regimes while class relativities are significantly sharper in the more affluent regimes. No single indicator is likely to prove adequate in capturing the diversity of experience of poverty and social exclusion in an enlarged European Union. The most effective strategy may be to take more seriously the need to translate the conceptually compelling case for a multidimensional approach to social exclusion into an appropriate set of operational alternatives.
Keywords: 330; economic vulnerability; poverty; social exclusion; welfare regimes; social class; Soziale Lage; Lebensstandard; Armut; Sozialstaat; Wirtschaftsverfassung; EU-Erweiterung; EU-Staaten